Internet reporting by state statutory bodies in Malaysia - Ahmad, Halimah @ Nasibah; Ismail, Mohamad Sharofi; Aripin, Norhani (Universiti Utara Malaysia, 2004)
Governments all around the world have embraced ICTs, especially the Internet, as a mean of making their operations more accountable and to provide the public with easier access to government services. Malaysia has taken its step by introducing Multimedia Super Corridor (MSC) in 1996 in order to speed up the process of Malaysia becoming a developed country. Malaysian Civil Service Link (MCSL) has also been formed and all government agencies were to establish and maintain their web sites before end of year 2000. This research is a descriptive study and the sample were all 130 State Statutory Bodies in Malaysia as reported in the Audit Report for the year ended 2001. Objectives of this study were to identify the number of state statutory bodies having web sites and to identify the type and extent of information disclosed on the web site. Findings of this study revealed that majority of the State Statutory bodies have website that are linked to MSCL but the accessibility of the web is not encouraging. It was also found that these bodies are keen to disclose non-financial information through their web sites only a small percentage disclosed summary of accounts that show figures on revenues and expenditures. It is hoped that this study will assist the government especially Malaysian Administration Modernization and Management Planning Unit (MAMPU) as a lead agency for the E-government flagship application in Malaysia to know the extent of implementation of Internet reporting by State Statutory Bodies after spending a lot of money in promoting electronic government.